PENGARUH TINGKAT PENDIDIKAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATA PELAJARAN MATEMATIKA SISWA KELAS XI SMA NEGERI 1 BANGGAI KABUPATEN BANGGAI LAUT - Zulvita Lestari Abdullah; Nurhayadi; Ibnu Hadjar (Jurnal Elektronik Pendidikan Matematika Tadulako, 2021)
This research aims to: (1) Find out whether there is an effect parental education level on learning achievement of XI grade students of SMA Negeri 1 Banggai, (2) find out whether there is an effect of learning motivation on learning achievement in XI grade mathematics at SMA Negeri 1 Banggai, (3) find out whether there is an effect of parents education level and learning motivation on learning achievement of XI grade mathematics subjects at SMA Negeri 1 Banggai. This research is a quantitative research using associative analysis technique with the research subjects being 56 student of class XI science. Data collection techniques using questionnaires and documentation. Research results show that (1) there is an effect of the variable level of parental education (X1) on the learning achievement of XI grade students in mathematics at SMA Negeri 1 Banggai, evidenced by the results of the partial test t arithmetic = 6,029 > t table 1,674 with a significant 0,000 < 0,05 which means H0 is rejected and Ha is accepted, (2) there is no influence of learning motivation variable on learning achievement of XI grade mathematic subjects at SMA Negeri 1 Banggai, evidenced by the results of the partial test t arithmetic = 1,457 < t table 1,673 with a significant 0,151 < 0,05 which means H0 is accepted and Ha is rejected, (3) there is a simultaneous influence of parents education level and learning motivation on learning achievement in mathematics for XI grade students of SMA Negeri 1 Banggai, evidenced by the results of the simultaneous test F count = 18,996 > F table 3,17 with a significant 0,000 < 0,05 so the H0 is rejected and Ha is accepted. The influence of parents education level on learning achievement is 39,68% greater than the influence of learning motivation on learning achievement which is 2,06%. The effect of parents education level and learning motivation simultaneously on learning achievement is 41,8% and the remaining 58,2% is influenced by other reasons not included in this study.